Entry of exotic insects into Australia: Does border interception count match incursion risk? - Caley, Peter; Ingram, Robert; De Barro, Paul (Biological invasions, 2015)
Interception data collected at the Australian quarantine border on the orders Coleoptera, Hemiptera, Lepidoptera and Diptera during 1986–2005 were cross-referenced to incursion data. For insects from these four orders, detection at the quarantine border was a poor predictor of successful incursions over the corresponding period. Most species that successfully mounted an incursion during the 1986–2005 period were not recorded as being intercepted at the quarantine border over the same period. This may be due to either organisms arriving via pathways that are not subject to border inspection, or that the inspection sensitivity is low, or that species discovered are not reliably identified, recorded and reported. The end result is that the border inspection, at least during the period 1986–2005, would have been largely ineffective as an early warning system for a large proportion of incursions occurring over that period. This finding is contrary to the expectation that interception data is a useful tool for predicting future incursions and opens the question as to whether different approaches to collecting interception data might improve predictive power. That said, within those species that were intercepted, those with a higher interception rate had an increased probability of a recorded incursion, particularly for incursions before 1986, and so supports the argument that propagule pressure is a key factor in invasion establishment.